Comparison of oliceridine and sufentanil in patient - controlled intravenous analgesia for post - thoracoscopic nausea and vomiting: a prospective, double - blind, randomized controlled trial - Meng, Yuxiang; Yuan, Sumin; Zhang, Hengrui; Ling, Zijie; Shi, Chenyang; Niu, Yang; Zhang, Li; Xu, Zhibiao; Liu, Yujun; Zhou, Kang; Liu, Su; Zhao, Linlin (Frontiers in Pharmacology, 2025)
ObjectiveTo compare oliceridine and sufentanil in patient-controlled intravenous analgesia (PCIA) for reducing postoperative nausea and vomiting (PONV) in thoracoscopic surgery patients.MethodsA prospective, double-blind, randomized controlled trial enrolled 130 patients at the Affiliated Hospital of Xuzhou Medical University from December 2024 to February 2025. Patients were randomly assigned to oliceridine (Group O, n = 65) or sufentanil (Group S, n = 65) PCIA groups. General anesthesia combined with nerve block anesthesia was used intraoperatively, followed by PCIA post-surgery. The primary outcome was PONV incidence within 48 h. Secondary outcomes included nausea and vomiting scores, pain scores, rescue analgesia and antiemetic use, recovery indicators, and adverse reactions.ResultsBaseline and intraoperative characteristics were similar between groups. The primary outcome (48-h PONV incidence) was significantly lower in Group O (32.3% [21/65]) than Group S (50.8% [33/65]; P = 0.033; OR = 0.46, 95% CI [0.23–0.94]), especially within 24 h postoperatively. Moderate-to-severe PONV was also less frequent in Group O (18.5% vs. 38.5%, P = 0.012; OR = 0.36, 95% CI [0.16–0.81]). Early postoperative pain scores were similar, but Group S had higher Visual Analogue Scale (VAS) scores after 12 h (P < 0.05), though the absolute differences were small (e.g., median resting VAS of 0 vs. 1 at 48 h). Rescue analgesic demand and PCIA use showed no significant difference. Group O had significantly higher Quality of Recovery-15 (QoR-15) scores (median difference at 24 h: 5.0 [95% CI 1.2–8.8]; P < 0.05) and significantly lower Athens Insomnia Scale scores (median difference at 24 h: 1.0 [95% CI -2.3 to −0.5]; P < 0.05) compared to Group S. Adverse reaction rates, including dizziness, nightmares, hallucinations, respiratory depression, dry mouth, allergy, and bradycardia, were similar between groups.ConclusionIn high-PONV-risk thoracoscopic surgery, oliceridine-based PCIA significantly reduced PONV incidence compared to sufentanil (32.3% vs. 50.8%, P = 0.033), while also demonstrating superior recovery quality (QoR-15) and sleep outcomes (AIS). This establishes oliceridine as a procedure-specific analgesic option for enhancing recovery beyond conventional opioid-sparing effects.